2015
DOI: 10.17265/2328-2150/2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Volatile Oil, Polyphenol Content and Antioxidant Activity in Extract of Laurus nobilis Grown in Iran

Abstract: Abstract:The leaves of Laurus nobilis were collected in the middle of four seasons (spring, summer, autumn, and winter) to determine the best harvesting time for obtaining the highest oil yield, 1,8-cineole and polyphenol content and antioxidant activity. After drying the plant materials in shade, their EOs (essential oils) were obtained by hydro-distillation method. Analysis of variance showed harvesting time had significant effect on the oil yields of L. nobilis. Seventy one components were identified in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…The EO content of laurel leaves was similar to that in some literature reports but different from other reports, most probably due to environmental and genotypic differences. Previous studies reported that the EO content of dried laurel leaves was 0.2% to 4.3% ( Abu-Dahab et al., 2014 ; Bahmanzadegan et al., 2015 ; El et al., 2014 ; Fidan et al., 2019 ; Shokoohinna et al., 2014 ; Vasundhara et al., 2016 ). The reported differences in the EO content and yield between this study and literature reports may also be due to environmental, harvest, and postharvest processing factors.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The EO content of laurel leaves was similar to that in some literature reports but different from other reports, most probably due to environmental and genotypic differences. Previous studies reported that the EO content of dried laurel leaves was 0.2% to 4.3% ( Abu-Dahab et al., 2014 ; Bahmanzadegan et al., 2015 ; El et al., 2014 ; Fidan et al., 2019 ; Shokoohinna et al., 2014 ; Vasundhara et al., 2016 ). The reported differences in the EO content and yield between this study and literature reports may also be due to environmental, harvest, and postharvest processing factors.…”
Section: Resultsmentioning
confidence: 96%
“…The essential oil (EO) content of laurel leaves has been reported to range between 0.2% and 4.3% depending on the location, harvesting time, and EO extraction type and conditions (e.g. hydrodistillation or steam distillation) ( Abu-Dahab et al., 2014 ; Bahmanzadegan et al., 2015 ; El et al., 2014 ; Fidan et al., 2019 ; Shokoohinna et al., 2014 ; Vasundhara et al., 2016 ). Previous research has shown that up to 270 EO constituents may be found in laurel leaves, the major ones being 1,8-cineole (22–56%), linalool (0.9–26.9%), α -terpinyl acetate (4.5–18.2%), α- pinene (2.2–15.9%), β- pinene (1.9–15.3%), sabinene (4.5–12.7%), α -terpineol (0.9–12.0%), terpineol-4 (0.9–4.1%) ( Abu-Dahab et al., 2014 ; Bahmanzadegan et al., 2015 ; Chahal et al., 2017 ; El et al., 2014 ; Fidan et al., 2019 ; Goudjil et al., 2015 ; Shokoohinna et al., 2014 ; Vasundhara et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The laurel EOs have demonstrated antimicrobial [14,15,16,17,18,24,26,29,30,31,32,33], antioxidant [12,15,16,20,21,23,26,32,33], and pharmacological properties [13,33]. Because of its biological activity, laurel leaf EO could be considered a natural supplement or antioxidant in cosmetics [1,34] and medicine [1,8].…”
Section: Introductionmentioning
confidence: 99%